Management of Education and Quality of Educational Services in Educational Institutions of the Puente Piedra District, Lima - Pacco , Rosa Angélica (2025)
The purpose of this research is to establish the relationship between educational management and the quality of educational services in schools in Puente Piedra, Lima. Specifically, it seeks to determine if there is a positive correlation between the way teaching is managed and the quality of the pedagogical services offered. The central objective was to analyze the link between these two factors, using five educational institutions in the Puente Piedra district as a reference and with the participation of 175 teachers. Quantitative approaches frame this ordinal-level study, employing a hypothetical-deductive method, a cross-sectional design, and a descriptive-correlational approach. Data collection was carried out using a structured questionnaire with a Likert-type scale. The validity of these instruments was reviewed by three specialists, and their reliability was verified using Cronbach's alpha coefficient, yielding a value of 0.789 for the first variable and 0.739 for the second. In the analysis phase, both descriptive and inferential statistical procedures were used. Spearman's rho coefficient was used, yielding a result of r = 0.326 with a significance level of 0.020, thus establishing a significant correlation between educational management and the quality of educational services in the educational institutions included in the study.